Is Thumb Proprioception Decreased in Patients With Trapeziometacarpal Joint Osteoarthritis?. Issue 4 (October 2020) - Seok, Hyun Sik; Lee, Kyoung Hwan; Lee, Yohan; Bae, Kee Jeong; Kim, Jihyeung; Gong, Hyun Sik
Abstract : Abstract: Proprioception is thought to be essential for normal joint homeostasis, and its decreased function has been associated with an increased risk of joint diseases. However, only a few studies have been performed on the association between proprioceptive function in the trapeziometacarpal joint (TMCJ) and osteoarthritis. The purpose of this study was to compare TMCJ proprioceptive function in elderly women with radiographic TMCJ osteoarthritis relative to age-matched control women without osteoarthritis. We enrolled 19 women (mean age, 66 years) with symptomatic, radiographic Eaton and Littler grade 2, 3, and 4 TMCJ osteoarthritis and 19 age-matched control women without osteoarthritis. We evaluated thumb proprioception by using a joint-position reproduction test and compared the reposition error (RE) between the groups. We carried out a multivariate analysis for factors potentially associated with increased RE, such as age, body mass index, hand dominance, the presence of diabetes, pain level, and the presence of osteoarthritis. Also, a logistic regression analysis was performed for factors associated with the occurrence of TMCJ osteoarthritis. Patients with TMCJ osteoarthritis had greater RE than did the control patients in the joint-position reproduction test at 20°, 30°, and 40° of thumb palmar abduction. The multivariate analysis indicated that increased RE was associated with the presence of osteoarthritis, but not with the other factors assessed. The occurrence of TMCJ osteoarthritis was associated with increased RE at 20°, 30°, and 40° of thumb palmar abduction. This study showed that decreased proprioceptive function was associated with the presence of osteoarthritis in the TMCJ, although the causality remains unknown. Further studies on the role of proprioception in the pathogenesis of TMCJ osteoarthritis and the potential role of its training for disease prevention or treatment are required.